Phylogenetic relationships of kaempferia plants based on inter-simple sequence repeat fingerprints - Orawan Theanphong (2019)
© 2018, Prince of Songkla University. All rights reserved. Plants in genus Kaempferia (Zingiberaceae) have been used as folk medicine in several countries. Identification and classification of Kaempferia plants are difficult because of the morphological similarity between species. In this study, phylogenetic relationships of Kaempferia species were employed by inter-simple sequence repeat (ISSR) fingerprints. Ten ISSR primers of 45 ISSR primers produced 186 bands with an average 19 bands per primer. The similarity index (SI) ranged from 0.0023-0.9950. A dendrogram was constructed using unweighted pair-group method of the arithmetic average (UPGMA). The results showed that the Kaempferia species could be divided into two main groups. The phylogenetic relationships were associated with the morphological characteristics.